Analysis of the Relationship between Fintech and Financing on MSME Performance - Almiranda Kadir; Echan Adam; Agustinus Moonti (Universitas KH. Abdul Chalim Mojokerto, 2025)
Modern trade currently encourages countries to continuously innovate to advance the economy, one of which is through strengthening the Micro, Small, and Medium Enterprises (MSMEs) sector. In facing these changing times, MSMEs are required to adapt to technological advances, particularly in the field of digital finance or financial technology (fintech). The use of fintech facilitates transaction processes and access to financing, which is expected to improve MSME performance. However, the use of fintech must be accompanied by adequate understanding and education for MSMEs. This study aims to analyze the influence of fintech and financing on MSME performance. The research used an explanatory approach with a quantitative approach using primary data. The results indicate that the use of fintech significantly influences financing, fintech directly influences MSME performance, and financing significantly influences MSME performance. Therefore, an active role is needed from local governments in providing accessible access to fintech services, affordable financing facilities, and entrepreneurship training to improve the competency of MSMEs in facing competition in the digital era.